Expressive means of the «object-event» data model - Yesin, V.I. (Radiotekhnika, 2017)
The relevance and importance of the problem of data representation in the subject domain modeling are shown. Expressive means (languages of conceptual modeling) are developed to represent conceptual models of subject domains in a graphic form, based on the "object-event" data model and being its constituent elements. Recommendations on their use are given.